The peptidyl-prolyl cis/trans isomerase Pin1 interacts with three early regulatory proteins of human cytomegalovirus - Schütz, Martin; Thomas, Marco; Wangen, Christina; Wagner, Sabrina; Rauschert, Luisa; Errerd, Theresa; Kießling, Melissa; Sticht, Heinrich; Milbradt, Jens; Marschall, Manfred (Virus Research, 2020)
Human cytomegalovirus (HCMV) is a ubiquitous human pathogen of high clinical relevance. Despite intensive research of virus-host interaction, crucial details still remain unknown. In this study, the role of the cellular peptidyl-prolyl cis/trans isomerase Pin1 during HCMV infection was investigated. Pin1 is able to recognize phosphorylated serine/threonine-proline motifs and regulates the structural conformation, stability and function of its substrates. Concerning HCMV replication, our recent studies revealed that Pin1 plays an important role in viral nuclear egress by contributing to the depletion of the nuclear lamina at distinct sites through the cis/trans conversion of lamin proteins. Here, novel data illustrate the HCMV-induced upregulation of Pin1 including various cell types being permissive, semi-permissive or non-permissive for productive HCMV replication. Addressing the question of functional impact, Pin1 knock-out (KO) did not show a measurable effect on viral protein expression, at least when assessed by Western blot analysis. Applying highly sensitive methods of qPCR and plaque titration, a pharmacological inhibition of Pin1 activity, however, led to a significant decrease of viral genome equivalents and production of infectious virus, respectively. When focusing on the identification of viral proteins interacting with Pin1 by various coimmunoprecipitation (CoIP) settings, we obtained positive signals for (i) the core nuclear egress complex protein pUL50, (ii) the viral mRNA export factor pUL69 and (iii) the viral DNA polymerase processivity factor pUL44. Confocal immunofluorescence analysis focusing on partial colocalization between Pin1 and the coexpressed viral proteins pUL50, pUL69 or pUL44, respectively, was consistent with the CoIP experiments. Mapping experiments, using transient expression constructs for a series of truncated protein versions and specific replacement mutants, revealed a complex pattern of Pin1 interaction with these three early regulatory HCMV proteins. Data suggest a combination of different modes of Pin1 interactions, involving both classical phosphorylation-dependent Pin1 binding motifs and additional phosphorylation-independent binding sites. Combined, these results support the concept that Pin1 may play an important role in several stages of HCMV infection, thus determining viral replicative efficiency.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Cytomegalovirus replication; Phosphorylation-independent interaction; Pin1 inhibitor-mediated viral replication block; Pin1 interaction with pUL50; Pin1 upregulation; Prolyl cis/trans isomerase Pin1; pUL44; pUL69